Concept Art Adaptasi dari Novel “Tujuh Kelana” Karya Nellaneva - Arrel Betha Anarsya; Dwi Mutia Sari (SENIMAN: Jurnal Publikasi Desain Komunikasi Visual, 2023)
"Tujuh Kelana" is a local novel by Nellaneva with the genre fantasy fiction. This novel was published on August 05, 2020. This novel was published in Jakarta by Elex Media Komputindo. The purpose of designing concept art adaptations of the novel "Tujuh Kelana" by Nellaneva is to visualize a written work into the form of concept art so that it can be glimpsed by creative industry players or entertainment developers to be used as works of adaptation of entertainment products such as films, animations, and video games. In the design of the concept art adaptation of the novel "Tujuh Kelana" by Nellaneva is a 4d development method consisting of Define, Design, Develop, and Disseminate. The data analysis method used in this design is SWOT analysis. The final result of this design is the main media in the form of artbooks and supporting media in the form of merchandise and informative print media.